PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI PRENDUAN I (SATU) KABUPATEN SUMENEP - Faizun Najah Faiz; Faizun Najah; Rofiadah Dafrojah (LPPM Universitas Cipta Mandiri, 2025)
Islamic Religious Education (IRE) at the elementary school level plays a crucial role in shaping students’ character and building a foundational understanding of Islamic teachings. However, its implementation often encounters various challenges, such as students’ low literacy in reading and writing the Qur’an, limited motivation to learn, and external environmental influences. These obstacles hinder the effectiveness of the learning process. Therefore, a more contextual and comprehensive approach is needed. This study aims to explore the challenges faced in the teaching of Islamic Religious Education and the efforts made by IRE teachers to address them at SD Negeri Prenduan I. The research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings reveal that Islamic Religious Education at SD Negeri Prenduan I encounters several significant issues. These include limited facilities and infrastructure, low student motivation, an overly dense curriculum, and insufficient variation in teaching methods. Additionally, students’ difficulties in understanding the material and differing learning styles further complicate the teaching process. To address these issues, teachers have taken several strategic measures, such as improved lesson planning, contextual teaching approaches, the use of interactive media, and hands-on learning through practice and simulation. Ongoing evaluations are also carried out to ensure that the learning process remains effective and responsive to students' needs. With flexible and targeted approaches, IRE instruction is expected to become more engaging, meaningful, and aligned with learners’ developmental stages.